Geological folds in three dimensions - Lisle, R. J. (TRABAJOS DE GEOLOGÍA, 2009)
The majority of terms that structural geologists use to describe the geometrical features of folds are defined in terms of simple cylindrical fold model. These terms have served well in the past where folds are observed at surface outcrop, and where three-dimensional information is limited. However, new mapping methods, e.g. high precision GPS, seismic and LIDAR deliver more complete 3D data on folded surfaces and reveal that the cylindrical model is an inadequate model of fold geometry.This review examines how existing terms such as the antiform, synform, hinge line and fold inflectionline can be re-defined in order to make them useful for describing general non-cylindrical folds.